The Ceramic legacy of Anna O. Shepard - Bishop, Ronald L.; Lange, Frederick W. 1944-. (Niwot, Colo. University Press of Colorado, 1991)
"Revised papers from a 1988 conference on the history of ceramic technology in archaeology. Part I examines Shepard's research, covering her contributions to Mesoamerican archaeology. Part II deals with current issues, including a discussion of Mesoamerican Plumbate Ware. Part III concludes with an assessment. In addition to valuable historical analysis, important theoretical and methodological issues are addressed"--Handbook of Latin American Studies, v. 57.
Revised papers presented at a conference held at the University of Colorado at Boulder in November 1988.
Keywords: Shepard, Anna Osler -- 1903-.; Pottery -- Analysis; Indian pottery -- Southwest, New; Indian pottery -- Central America